Constructing a Model Combining Zalo and End-to-End Encryption for Application in Digital Transformation - Vinh, Cao Thanh; Huong, Pham Van (Journal of Science and Technology on Information security, 2023)
Abstract—This paper proposes and implements a model combining Zalo and end-to-end encryption to apply in digital transformation. The main idea is to promote the strengths of the Zalo social network to exchange information and manage work but ensure information confidentiality for both the server and man-in-the-middle attacks based on the end-to-end encryption model. End-to-end encryption is right at the client, so only the encrypted data is stored on the server and therefore the server cannot decrypt it. This solution can use international standard cryptographic algorithms or those of the Vietnam Government Information Security Commission. The solution model has been developed, deployed, and tested at the Academy of Cryptography Techniques. Our proposed system serves as an end-to-end encryption and adapter used to encrypt text data and files in various social networks. Within the scope of this paper, we deploy a test solution with Zalo.